Editorial - Sandra Josefina Ferraz Ellero Grisi (University of São Paulo, 2011)
The study of pathology plays a fundamental role in the training and continuing education of physicians, because it is the area of knowledge concerned with the morphology of organs and tissues, identifying relationships between structure and function, encompassing the mechanism of disease. Pathology is the principal link between basic science and clinical medicine, promoting accurate, effective practices in patient care.